Enhancement of a leg-wheel mechanism by hydraulics toward compliantly balancing platforms for heavy duty work. (2nd December 2021) - Oda, Kengo; Yasui, Yuya; Kurose, Yuichiro; Hyon, Sang-Ho
Abstract : This paper presents CRAWHEL, a proposed low-height leg-wheel platform for dexterous and safe construction work. The platform supports most of its weight with two large wheels in the center and crawling in a low position with four hydraulically driven legs. By actively manipulating the contact force of legs and wheels by hydraulic joint torque control, the body can respond to unexpected reaction forces and to sudden changes in terrain shape. Thereby, it maintains the position and orientation stably while generating necessary force to the work tools. This paper describes the design concept and verifies it using preliminary simulations and experiments. For this purpose, the first hardware prototype with 16 degrees of freedom, 2 m length, 660 mm height, and 145 kg weight was fabricated. Details of the hardware and the whole-body motion control method are presented herein. Numerical analysis underscores the effectiveness of leg-wheel coordinated control for the most commonly used horizontal sway motions. The experimentally obtained results demonstrate that the prototype can maintain the position and posture of the base even if the ground actually moves irregularly, or if a strong disturbance is applied. GRAPHICAL ABSTRACT: UF0001